Maksimalisasi Pendapatan Daerah dari Retribusi IMB di DKI Jakarta (Studi Komparatif Antar Kota Administrasi) - Mulia Rahmah, SKom., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
Maximizing revenue acquisition is often viewed as one of the prerequisites for the implementation of regional development. However, in the process of maximizing revenue trapped many local governments in the region extending activities income which is exploitative and tend to conflict with higher laws. The purpose of this study is to analyze one of the building permit levies that affect local revenue. This study uses the Regional Income as the dependent variable, while Building Permit (Levies Development Supervision and Levies Building Control) as independent variables, which the IMB is very influential on regional income.